Association of work performance with absenteeism and presenteeism among support workers in a medical school hospital, Thailand - Tangchareonsamut J. (2023)
Purpose: The aim of the study is to determine the prevalence of absenteeism and presenteeism and explore their association with work performance among support workers in a medical school hospital in Thailand. Design/methodology/approach: A cross-sectional study was conducted among 1,102 support workers in the Faculty of Medicine Ramathibodi Hospital, Mahidol University, in June–August 2020. The World Health Organization Health and Work Performance Questionnaire (HPQ) was used to assess absenteeism, presenteeism, work performance and related factors. Multiple logistic regression was used to examine the association between current work performance and absenteeism and presenteeism in the past year. Findings: A total of 505 (45.8%) support workers completed the self-report questionnaire. Prevalence of sickness absence, non-sickness absence and presenteeism in the past year was 54.2%, 81.4% and 48.1%, respectively. Sickness absence and presenteeism in the past year were significantly associated with increased odds of poor work performance: (OR 3.05, 95% CI: 1.24–7.49) and (OR 5.12, 95% CI: 2.25–11.64), respectively. Support workers with high levels of stress and burnout were 3.89 (95% CI: 1.56–9.68) and 2.66 (95% CI: 1.50–4.72) times more likely to report poor work performance. Originality/value: Sickness absence and presenteeism are associated with poor work performance in hospital support workers. Other factors such as stress and burnout also contribute to poor work performance, and interaction among these factors needs further research. To improve productivity, hospital administrators might consider intervention programs to enhance work performance among workers with sickness absence and presenteeism.